Shape of the self-concept clarity change during group psychotherapy predicts the outcome: an empirical validation of the theoretical model of the self-concept change - Styła, Rafał (Frontiers in Psychology, 2015)
Background: Self-Concept Clarity (SCC) describes the extent to which the schemas of the self are internally integrated, well defined, and temporally stable. This article presents a theoretical model that describes how different shapes of SCC change (especially stable increase and “V” shape) observed in the course of psychotherapy are related to the therapy outcome. Linking the concept of Jean Piaget and the dynamic systems theory, the study postulates that a stable SCC increase is needed for the participants with a rather healthy personality structure, while SCC change characterized by a “V” shape or fluctuations is optimal for more disturbed patients. Method: Correlational study in a naturalistic setting with repeated measurements (M = 5.8) was conducted on the sample of 85 patients diagnosed with neurosis and personality disorders receiving intensive eclectic group psychotherapy under routine inpatient conditions. Participants filled in the Self-Concept Clarity Scale (SCCS), Symptoms' Questionnaire KS-II, and Neurotic Personality Questionnaire KON-2006 at the beginning and at the end of the course of psychotherapy. The SCCS was also administered every 2 weeks during psychotherapy. Results: As hypothesized, among the relatively healthiest group of patients the stable SCC increase was related to positive treatment outcome, while more disturbed patients benefited from the fluctuations and “V” shape of SCC change. Conclusions: The findings support the idea that for different personality dispositions either a monotonic increase or transient destabilization of SCC is a sign of a good treatment prognosis.